Breast Carcinoma Cells in Primary Tumors and Effusions Have Different Gene Array Profiles. (6th August 2009) - Konstantinovsky, Sophya; Smith, Yoav; Zilber, Sofia; Tuft Stavnes, Helene; Becker, Anne-Marie; Nesland, Jahn M.; Reich, Reuven; Davidson, Ben
Abstract : The detection of breast carcinoma cells in effusions is associated with rapidly fatal outcome, but these cells are poorly characterized at the molecular level. This study compared the gene array signatures of breast carcinoma cells in primary carcinomas and effusions. The genetic signature of 10 primary tumors and 10 effusions was analyzed using the Array-Ready Oligo set for the Human Genome platform. Results for selected genes were validated using PCR, Western blotting, and immunohistochemistry. Array analysis identified 255 significantly downregulated and 96 upregulated genes in the effusion samples. The majority of differentially expressed genes were part of pathways involved in focal adhesion, extracellular matrix-cell interaction, and the regulation of the actin cytoskeleton. Genes that were upregulated in effusions included KRT8, BCAR1, CLDN4, VIL2, while DCN, CLDN19, ITGA7, and ITGA5 were downregulated at this anatomic site. PCR, Western blotting, and immunohistochemistry confirmed the array findings for BCAR1, CLDN4, VIL2, and DCN . Our data show that breast carcinoma cells in primary carcinomas and effusions have different gene expression signatures, and differentially express a large number of molecules related to adhesion, motility, and metastasis. These differences may have a critical role in designing therapy and in prognostication for patients with metastatic disease localized to the serosal cavities.